The Spemann organizer gene, Goosecoid, promotes tumor metastasis - Hartwell, Kimberly A. (National Academy of Sciences, 2006)
The process of invasion and metastasis during tumor progression is often reminiscent of cell migration events occurring during embryonic development. We hypothesized that genes controlling cellular changes in the Spemann organizer at gastrulation might be reactivated in tumors. The Goosecoid homeobox transcription factor is a known executer of cell migration from the Spemann organizer. We found that indeed Goosecoid is overexpressed in a majority of human breast tumors. Ectopic expression of Goosecoid in human breast cells generated invasion-associated cellular changes, including an epithelial–mesenchymal transition. TGF-β signaling, known to promote metastasis, induced Goosecoid expression in human breast cells. Moreover, Goosecoid significantly enhanced the ability of breast cancer cells to form pulmonary metastases in mice. These results demonstrate that Goosecoid promotes tumor cell malignancy and suggest that other conserved organizer genes may function similarly in human cancer.